Reduced NKX2.1 Expression Predicts Poor Prognosis of Gastric Carcinoma - Zhao, Bai-Wei (PLoS One, 2014)
Thyroid transcription factor-1 (NKX2.1/TITF-1) is a member of the thyroid tissue-specific transcription factor family that has been proven to be closely associated with many human diseases. Recently, it was reported that NKX2.1 expression is lost or reduced in some human cancers such as lung cancer and thyroid cancer. However, there was insufficient data to suggest that NKX2.1 functionality could be used as a prognostic factor. Therefore, this study aims to investigate NKX2.1 expression and its prognostic significance in primary gastric carcinoma. Then, we attempted to investigate if NKX2.1 expression was related to the clinicopathological characteristics and prognosis of gastric carcinoma (GC)patients. The expression levels of NKX2.1 were analyzed in tissue samples from 205 gastric carcinoma patients by real-time quantitative PCR (qRT-PCR), Western blotting, and immunohistochemical staining(IHC). Our qRT-PCR results showed that the expression of NKX2.1 mRNA was reduced in tumor tissue samples compared with that in matched adjacent non-tumor tissue samples (P<0.001); this finding was confirmed by Western blot analysis (P<0.001). Our immunohistochemical staining data indicated that NKX2.1 expression was significantly decreased in 87 of 205 (42.4%) gastric carcinoma cases. Kaplan-Meier survival curves revealed that the decreased expression of NKX2.1 was significantly associated with poor prognosis in gastric carcinoma patients (P<0.001). Multivariate Cox analysis identified NKX2.1 expression as an independent prognostic factor for overall survival (P = 0.005). Furthermore, the functions of Nkx2.1 were analyzed with respect to the proliferation, migration, and invasion of GC cell lines. Our data suggest that NKX2.1 may function as a tumor suppressor in primary gastric carcinoma and that its reduced expression independently predicts an unsatisfactory prognosis in gastric carcinoma patients.